Construct validity evidence for a measure of peer athletic reputation (PAthR) in high school physical education. (May 2016) - Howle, Timothy C.; Whipp, Peter R.; Gairns, Felicity; Thornton, Ashleigh L.; Rebar, Amanda L.; Jackson, Ben
Abstract: Grounded in the work that has been conducted on peer academic reputation in educational settings, our aim was to develop and provide initial construct validity evidence for a modified instrument designed to assess peer athletic reputation (PAthR). In phase 1, we devised a series of items to assess PAthR. In phase 2 ( n = 399), and approximately one month later in phase 3 ( n = 374), female high school physical education (PE) students completed a series of questionnaires that included the PAthR instrument. Analyses indicated that PAthR was (a) represented as a unitary construct, (b) positively associated across time points, (c) positively associated with indicators of desirable peer interactions (e.g., peer relatedness support, peer relatedness need satisfaction) and PE experiences (e.g., intrinsic motivation, perceived competence), and (d) negatively associated with indices considered to be less adaptive in nature (i.e., anxiety, amotivation). These findings provide preliminary support for a novel approach to the measurement of peer reputation in PE, and demonstrate evidence of the nomological net with which this concept may be associated. Highlights: We present an instrument designed to assess peer athletic reputation (PAthR). We describe instrument development and examine construct validity. PAthR was positively associated across time points. PAthR was positively associated with desirable peer- and PE-based indicators. PAthR was negatively associated with less desirable peer- and PE-based indicators.